Soil Contamination in Randukuning Landfill: Morphological-Physiological Responses of Celosia argentea L. and Cleome rutidosperma D.C. - Hayati, Dwi Puji; Nugroho, Andhika Puspito (UIN Sunan Gunung Djati Bandung, 2022)
The soil in the Landfill area has generally been contaminated by various types of pollutants, including heavy metals, microplastics, ammonia, chloride, benzene, toluene, ethylene, ethylene benzene, and xylene (BTEX). At high concentrations, the pollutant can cause toxic effects on plants. The study aimed to evaluate the morphological and physiological conditions of C. argentea L. and C. rutidosperma D.C. after being planted on Randukuning landfill soil. Plant species were planted on landfill soil in the greenhouse for two months. Morphological observations (stem length, root length, and the number of leaves) and physiological (biomass of roots, stems, and leaves) were carried out on days 0, 3, 7, 14, 21, and 28 after planting on landfill soil. The results showed that C. argentea L. and C. rutidosperma D.C. did not show morphological and physiological effects. Both species can grow well on landfill soils. Therefore, these species can be potential phytoremediation agents.